2015
DOI: 10.5301/hipint.5000299
|View full text |Cite
|
Sign up to set email alerts
|

Hip Arthroscopy in Osteoarthritis: A Systematic Review of the Literature

Abstract: The quality of studies is low. We have found inconclusive evidence to make categorical indications for hip arthroscopy in the treatment of OA, although we have found that there is some postoperative clinical outcome improvement of pain and function in a short-term evaluation. Increasingly worse outcomes were seen as the severity of OA increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
0
18
1
Order By: Relevance
“…Although we have found that there is some postoperative clinical outcome improvement of pain and function in a short-term evaluation, increasingly worse outcomes where seen as the severity of OA increased. At the present we found that level of evidence is low to support the indication a hip arthroscopy in the presence of advanced preoperative osteoarthritis 20 . Labral and chondrolabral lesions were the most frequent intraoperative findings in our series.…”
Section: Discussioncontrasting
confidence: 54%
“…Although we have found that there is some postoperative clinical outcome improvement of pain and function in a short-term evaluation, increasingly worse outcomes where seen as the severity of OA increased. At the present we found that level of evidence is low to support the indication a hip arthroscopy in the presence of advanced preoperative osteoarthritis 20 . Labral and chondrolabral lesions were the most frequent intraoperative findings in our series.…”
Section: Discussioncontrasting
confidence: 54%
“…On the contrary, patients with a joint space wider than 2 mm significantly improved the mHHS, Short Form 12 and HOS scores at 3-year follow-up. This means that age did not constitute an independent risk factor for articular failure, but only if related with a severe joint space narrowing; as reported by the former systematic review [24]. However, a retrospective study on hip preservation following hip arthroscopy at 5-year follow-up evidenced that age older than 45 at the time of surgery was an independent risk factor for THA [37].…”
Section: Discussionmentioning
confidence: 95%
“…Studies regarding clinical outcomes after hip arthroscopy in middle-aged patients with early osteoarthritis of various diagnoses are uncommon 15,16) . This study demonstrates that:…”
Section: Discussionmentioning
confidence: 99%
“…Although pain and clinical symptoms improve after hip arthroscopy, surgical outcomes in patients with more severe osteoarthritis became worse 15,16) . Horisberger et al 22) identified that those with Tönnis grade III have poorer prognoses compared with those with Tönnis <III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation